Efficacy of three modern anti-diabetic drugs on survival outcomes of lung cancer patients with type 2 diabetes in China - Chen, Zijia; Sun, Ziyi; Zhang, Zhongtao; Lei, Chao; Ren, Zhewen; Di, Yupeng; Wang, Zhifei (Frontiers in Oncology, 2025)
BackgroundSome anti-diabetic drugs have been proved to be a tumor suppressor or activator. The associations of three relatively new classes of anti-diabetic medications–glucagon-like peptide-1 receptor agonists (GLP-1RA), dipeptidyl peptidase 4 inhibitors (DPP-4I), and sodium-glucose cotransporter 2 inhibitors (SGLT-2I) with lung cancer prognosis remain unclear.MethodsThe electronic medical data from the National Healthcare Big Data (East) Center was retrospectively analyzed. We included 11,357 newly diagnosed lung cancer patient with type 2 diabetes (T2D) between January 1st, 2020 and July 1st, 2023. Patients were categorized into eight groups according to the mono-or-combination therapy of GLP-1RA, DPP-4I and SGLT-2I. Disease progression and mortality risk were evaluated by cox proportional hazards analysis. Progression-free survival (PFS) and overall survival (OS) were assessed by the Kaplan-Meier (log-rank) method.ResultsLung cancer patients with T2D who were treated with SGLT-2I & GLP-1RA exhibited the lowest progression (hazard ratio [HR]: 0.37; 95% confidence interval [CI]: 0.18, 0.78) and mortality risks (HR: 0.34; 95% CI: 0.14, 0.82) as well as prolonged median PFS (1.55 years) and OS (1.62 years) among all groups. In contrast, DPP-4I monotherapy did not show benefit for progression (HR: 1.09; 95% CI: 0.98, 1.22. Median PFS: 1.41 years) and mortality risks (HR: 0.96, 95%CI: 0.84, 1.09. Median OS: 1.48 years). However, when DPP-4I was used in combination with SGLT-2I or GLP-1RA, it caused reductions in both progression and mortality risks.ConclusionSGLT-2I & GLP-1RA dual therapy is associated with improved prognosis for lung cancer patients with concurrent T2D. DPP-4I transits from a tumor activator to suppressor when combined with other anti-diabetic drugs. Future studies are needed to examine the underlying biological mechanisms.